PENGARUH PENERAPAN PENDIDIKAN KARAKTER MELALUI STRATEGI INKUIRI TERBIMBING PADA MATERI LARUTAN ELEKTROLIT DAN NON ELEKTROLIT - Belviyani, Jenny; Utami, Lisa (JURNAL EKSAKTA PENDIDIKAN (JEP), 2017)
This research was a quasi-experiment instigated by the low of student character building.  This research aimed at knowing the effect of implementing character building through guided inquiry strategy on electrolyte and non-electrolyte solution material at state senior high school 9 pekanbaru that characters studied were honesty, responsibility, cooperation, discipline, and curiosity.  Purposive sampling was used in this research, and there were two classes of samples selected that the tenth grade of Natural Science 4 was as the experimental group taught by implementing Character Building through Guided Inquiry strategy and Natural Science 3 was as the control group taught by using discussion, question and answer methods. This research was conducted for three meetings.  Documentation and observation were the techniques of collecting the data.  T-test was used to know the research findings of student communication skill.  Final data processing results showed that tobserved was 2.19 and ttable was 1.99, and it revealed that tobserved was higher than ttable. Ho was rejected and Ha was accepted.  There was an effect of implementing Character Building through Guided Inquiry strategy on Electrolyte and Non-Electrolyte Solution material at State Senior High School 9 Pekanbaru, and its coefficient effect was 5.86%.